PENGARUH PERPUTARAN KAS, MODAL KERJA, PERPUTARAN PIUTANG DAN PERPUTARAN AKTIVA TERHADAP PROFITABILITAS PADA PERUSAHAAN PERKEBUNAN DAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2015 - Nirmala Sari (Bis-a, 2022)
The purpose of this study is to test and analyze the effect of cash turnover, working capital, receivable turnover, asset turnover to profitability in plantation and mining companies listed in Indonesia Stock Exchange Period 2011-2015. This research uses quantitative research approach. The population of this research is 48 plantation and mining companies and the sample of this research is 9 Plantation and mining companies. The result of the research shows that cash turnover is partially significant and significant to profitability in plantation and mining companies listed in Indonesia Stock Exchange in the period of 2011-2015. Working capital and partially receivable turnover have no significant effect on profitability in plantation and mining companies listed in Indonesian Stock Exchange for the period 2011-2015. Asset turnover partially significant effect on profitability in plantation and mining companies listed in Indonesia Stock Exchange in the period of 2011-2015. Cash turnover, working capital, receivable turnover, simultaneously asset turnover have a significant effect on profitability at plantation and mining companies listed in Indonesia Stock Exchange in the period of 2011-2015.